Manchas necróticas en hojas de plantas adultas de cacao (Theobroma cacao L.) causadas por Rhizoctonia sp. - Salas, A. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Leaf spots different from those caused by known cacao diseases were found at Turrialba and other locations in Costa Rica. Rhizoctonia sp., was consistently isolated from affected leaves. The symptoms consist of round to irregular brown to black lesions and were reproduced in disease free leaves inoculated with cultures of Rhizoctonia isolate. Rhizoctonia sp. was recuperated from these lesions. There is no previous report of Rhizoctonia causing a cacao leaf disease.